Test automation fundamentals : a study guide for the certified test automation engineer exam - Baumgartner, Manfred; Steirer, Thomas; Wendland, Marc-Florian; Gwihs, Stefan; Hartner, Julian; Seidl, Richard (dpunkt, 2022)
Test automation is an essential tool in today’s software development environments. It increases testing efficiency and makes test procedures reliably repeatable. This book provides a complete overview of how to design test automation processes and integrate them into your organization or existing projects. It details functional and technical strategies and goes into detail on the relevant concepts and best practices. The book’s main focus is on functional system testing. The appendix contains an overview of software quality characteristics according to the ISO 25010 standard, and lists potential test automation applications within this context. It also provides an introduction to load and performance testing, and a sample catalog of criteria for selecting test automation tools. This book is fully compliant with the ISTQB® syllabus and, with its many explanatory examples, is equally suitable for preparation for certification, as a concise reference book for anyone who wants to acquire this essential skill, or for university-level study.